Computational Strategy For Rehabilitation Of Reinforced Concrete Framed Structure Using Fibre Reinforced Polymer Confinement Of Columns - Seyedasaei, Seyedmohsen (2014)
Fibre Reinforced Polymer (FRP) has been widely used for retrofitting of reinforced concrete (RC) columns. However, the global response of retrofitted RC framed structure based on Displacement Based Design (DBD) method is not clearly known. In addition, reducing consumption of material and analysis time should be taken into account. Thus, this study is aimed to determine the global response of retrofitted structure using FRP-confined columns when nonlinear analysis is used to assess the structure. The analysis results for FRP-confined RC columns were first verified using eighteen experimental results found in literature. The analysis was then proceeded to the whole RC frame consisting of three to seven storey levels. The global response of retrofitted RC frame using FRP-confined columns has been found to be identical in post-yield envelope at pushover curve in conventional and ADRS formats without changing in initial stiffness. Response of retrofitted RC frame was firstly verified using analytical solution. A systematic procedure was then developed for seismic rehabilitation of RC frame based on both linear and nonlinear methods of assessment. Four case studies were used to demonstrate the applicability of proposed systematic procedures for linear and nonlinear methods of assessment. It was found that retrofitting using nonlinear method give less material consumption as compared to linear method. However, the computational time increases substantially. Results of the current study have demonstrated that the proposed systematic rehabilitation procedure for RC framed structure using FRP is capable to reach its performance objective using less material as well as computational time.